Exploring the roles of Special Schools' principals in Student quality improvement: A case study of Special Schools - sahuddin, Muhammad Sahuddin; Cheng Jinkuan, Cheng Jinkuan; Verawati, Verawati (Universitas Ahmad Dahlan, 2023)
This qualitative research aimed to explore the principal's role in improving the quality of students at the Southwest Aceh public special school. In particular, this study discusses the role of school principals as educators, managers, administrators, supervisors, leaders, innovators, and motivators in improving student quality with the main research question what is the role of school principals in improving student quality? This research was conducted using a case study design. Data was collected through in-depth interviews with school principals, supervisors, vice principals, and teachers, as well as observing and reviewing existing documents and literature on the role of the principal. The research findings reveal the school principal's role in improving students' quality, namely that the principal cares about harmonization with students, guides, provides motivation and creates learning programs and skills that can improve student quality. In addition, the results of this study also found that the school principal also administered the data of tipped students and provided rewards and punishments for students who violated school rules. In addition, the findings of this study also found that there were obstacles to improving student quality, namely the management of students in the teaching and learning process united in one class, not based on disabilities. Students mixed with deaf, mentally retarded, disabled, and autistic students are in one class taught by one class teacher, so the achievement of learning objectives is very difficult to realize, and the teacher is very difficult to handle students. The findings from this study have significant implications for the role of school principals in improving student quality because school principals are the most crucial element in schools for improving student quality. Therefore, this study recommends increasing the role of school principals in improving the quality of students for the benefit of Indonesia as a whole.